PRESERVATION OF LOCAL LEADERSHIP VALUES OF THE AMMATOA INDIGENOUS PEOPLE, KAJANG DISTRICT, BULUKUMBA REGENCY - Sari, Nirmala; Guntur, Muhamamd; Yamin, Muh Nur; Fitri, Anisa (Universitas Negeri Makassar, 2025)
This study aims to describe traditional leadership values in the Kajang customary community in Bulukumba. The research method used is descriptive qualitative and data collection techniques, in the form of: observation, interviews, and literature study. The research result showed that there are six traditional leadership values in Kajang custom community, such as: honesty, firmness, unity, simplicity, patience and care for the natural environment. The honesty value is the primary value that must be practiced in everyday life, likes honest to Turiek Akrana, honest to human beings, and honest to ourself. The firmness value must be owned by leader to do justice to many people. The unity value must be upheld as a sense of solidarity and life hormony ini society. The simplicity value must be realized in daily life according to the guidance of pasang. The patience value must be practiced, primarily to Ammatoa, to accept the fate from Turiek Akrakna. The care for natural environment value is a realization act in preserving the natural environment according to the guidance of pasang.